DEBT GOVERNANCE AS A DYNAMIC SYSTEM: RISK MITIGATION AND VALUE CREATION IN MEDIUM-SIZED ENTERPRISES - Borges, Leandro (Humanas em Perspectiva, 2026)
Debt management is a field of tension between the pursuit of growth and the need for risk control. In medium-sized enterprises, this tension is amplified by the combination of expansion ambitions and greater vulnerability to shocks. Reactive and fragmented debt management emerges as a primary source of financial risk. Through a systematic literature review, based on the PRISMA protocol and a thematic analysis of 42 articles, we critically investigate the pillars of debt management: capital structure theories, debt architecture, and the ambivalent role of covenants. Our analysis reveals not only fragmentation in the literature but also inherent paradoxes, such as the fact that control mechanisms (covenants) can induce risky behaviors (earnings management). We propose, as a theoretical contribution, a Dynamic Debt Governance Framework (DDGF), which conceptualizes debt management not as a sequence of phases, but as an adaptive and cyclical system. The framework explores the interdependencies and feedback loops between the Strategy, Structuring, and Monitoring phases, positioning debt management as a continuous organizational learning process. We delve into the specific implementation challenges for medium-sized enterprises and conclude with a research agenda focused on the empirical validation of the framework and the impact of technology on the automation of debt governance.